Pemanfaatan Tik Dalam Mendukung Pembelajaran Dari Rumah - Kuswanto, Joko; Yunarti, Yelmi; Adesti, Anita (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2021)
The rapid development of ICT allows the implementation ofvarious ways to become more efficient, one of which is in the world ofeducation. ICT itself must be mastered as part of a discipline that hasvarious functions as a tool for users (educators and learners) in thelearning process. The teaching and learning process is now not onlydone face-to-face but can also be done with the use of technology suchas online learning, among others, with social media, onlineconferences and learning management systems (LMS). With the onlinelearning process, it is necessary to do counseling and training relatedto the use of ICT in supporting online learning. This activity is carriedout in the hope of facilitating the learning process for both studentsand teachers to stay connected, both inside and outside the classroom.The result of the activities that have been carried out is that citizensalready understand and understand about the use of ICT to supportlearning from home.